Progesterone Exerts a Neuromodulatory Effect on Turning Behavior of Hemiparkinsonian Male Rats: Expression of 3α-Hydroxysteroid Oxidoreductase and Allopregnanolone as Suggestive of GABAA Receptors Involvement - Roberto Yunes; Sebastián Casas; Eliana Gaglio; Ricardo Cabrera (Parkinson's Disease)
There is a growing amount of evidence for a neuroprotective role of progesterone and its neuroactive metabolite, allopregnanolone, in animal models of neurodegenerative diseases. By using a model of hemiparkinsonism in male rats, injection of the neurotoxic 6-OHDA in left striatum, we studied progesterone’s effects on rotational behavior induced by amphetamine or apomorphine. Also, in order to find potential explanatory mechanisms, we studied expression and activity of nigrostriatal 3α-hydroxysteroid oxidoreductase, the enzyme that catalyzes progesterone to its active metabolite allopregnanolone. Coherently, we tested allopregnanolone for a possible neuromodulatory effect on rotational behavior. Also, since allopregnanolone is known as a GABAA modulator, we finally examined the action of GABAA antagonist bicuculline. We found that progesterone, in addition to an apparent neuroprotective effect, also increased ipsilateral expression and activity of 3α-hydroxysteroid oxidoreductase. It was interesting to note that ipsilateral administration of allopregnanolone reversed a clear sign of motor neurodegeneration, that is, contralateral rotational behavior. A possible GABAA involvement modulated by allopregnanolone was shown by the blocking effect of bicuculline. Our results suggest that early administration of progesterone possibly activates genomic mechanisms that promote neuroprotection subchronically. This, in turn, could be partially mediated by fast, nongenomic, actions of allopregnanolone acting as an acute modulator of GABAergic transmission.